Phenotypic and genetic features of enteropathogenic Escherichia coli isolates from diarrheal children in the Ribeirao Preto metropolitan area, Sao Paulo State, Brazil - Pitondo-Silva, Andre; Nakazato, Gerson; Falcao, Juliana P.; Irino, Kinue; Martinez, Roberto; Darini, Ana Lucia C.; Hernandes, Rodrigo Tavanelli [UNESP] (Wiley-Blackwell, 2015)
This study was designed to characterize a collection of 60 enteropathogenic Escherichia coli (EPEC) isolates from diarrheic feces of patients in the RibeirAo Preto metropolitan area regarding different phenotypic and molecular features. We examined antibiotic resistance profiles, occurrence of virulence factors-encoding genes, intimin subtypes and the correlation of serotypes among typical (tEPEC) and atypical (aEPEC) EPEC isolates. The results demonstrated that atypical EPEC was more heterogeneous than typical EPEC concerning the characteristics investigated and 45.2% do not belong to classical EPEC serogroups. Intimin subtype was the most frequent among the EPEC isolates (46.7%), being detected in both tEPEC and aEPEC. The majority of aEPEC isolates presented localized adherence-like (LAL) pattern to HEp-2 cells, although aEPEC isolates displaying diffuse adherence (DA) or non-adherent were also detected. High prevalence of antimicrobial resistance was found for ampicillin, cephalothin, sulfonamide and tetracycline. In general, tEPEC isolates were more resistant to the antimicrobials tested than aEPEC isolates.
Keywords: Enteropathogenic E; Coli; Serotypes; Antimicrobial resistance; Intimin; Typical and atypical EPEC